Phenomenology and Anthropology in Foucault's “Introduction to Binswanger's Dream and Existence“: A Mirror Image of the Order of Things? - Han-Pile, Béatrice (History and theory, 2016)
In this article, I examine the relation between phenomenology and anthropology by placing Foucault's first published piece, “Introduction to Binswanger's Dream and Existence“ in dialectical tension with The Order of Things. I argue that the early work, which so far hasn't received much critical attention, is of particular interest because, whereas OT is notoriously critical of anthropological confusions in general, and of “Man” as an empirico-transcendental double in particular, IB views “existential anthropology” as a unique opportunity to establish a new and fruitful relation between transcendental forms and empirical contents. This is because IB focuses on a specific object, “Menschsein” (the “being of man”), which is neither the transcendental subject nor an empirical being (a member of the class Homo sapiens). Thus for the young Foucault, existential anthropology occupies a fertile methodological middle ground between transcendental approaches (exemplified in IB by Heideggerian phenomenology) and empirical forms of analysis (exemplified by Freudian psychoanalysis). I first interpret anthropology in the light of phenomenology and defend the view that Menschsein is neither a transcendental structure nor a concrete particular, but the instantiation of the first in the second. I argue that for anthropology to yield the full theoretical benefits Foucault claims for it, the particular cases of Menschsein examined in existential analysis have to be regarded as exemplary. I then read phenomenology back in the light of anthropology and examine how, for Foucault, the analysis of Menschsein in dreams benefits fundamental ontology by affording us a clearer view of some of the main existentiale than the focus on everyday waking experience in Being and Time. Finally, I turn to the limits and difficulties of this early position and my reading of it, and to their consequences for Foucault's later view.